Living your own life : existential analysis in action - Laengle, Silvia; Wurm, Christopher (Karnac Books Ltd, 2016)
This multi-author anthology is a short introduction to the world of existential psychotherapy, and specifically Existential Analysis. It gives concrete answers and demonstrates a way to apply this thinking in practice, providing outlines of its theoretical background, including Alfried Langle's four fundamental motivations. The main themes of the book are: working with emotionality and subjective experience and its importance for a fulfilling life; meaning and happiness; and spirituality and temporality. It covers psychological disorders and their treatment in adults and children, and also deals with disability and handicap.